EFEK MODERASI GENDER PADA PENGARUH INDEPENDENSI TERHADAP KUALITAS AUDIT - Silmi, Silmi; Yurniwati, Yurniwati; Oktavia, Fitriyeni; Ramdany, Kevry; Komalasari, Sanda Patrisia; Fajri, Aulia; Aulia, Siti (Ensiklopedia of Journal, 2023)
This research aims to reveal the moderating effect of gender on the influence of independence on audit quality. This type of research is descriptive and associative research. The sample in this research is State Civil Apparatus (SCA) as internal auditors who work at the Bukittinggi City Inspectorate Office. The sample was selected using a random sampling method of 30 respondents. The data source for this research is primary data from a questionnaire that was announced to respondents with closed questions and secondary data from documentation. The data analysis technique used in this research is quantitative analysis using the Structural Equation Model (SEM) or variant-based Structural Equation Model which can simultaneously test the measurement model as well as test the structural model. The research results reveal that independence has a positive effect on audit quality and female gender is more likely to moderate the influence of independence on audit quality than male gender.